Pengaruh Latihan Plyometric Jump To Box dan Hurdle Jump terhadap Tinggi Loncatan Pemain Sekolah Sepak Bola Gerzy Star - Nuris Mahendra Putra; Olivia Andiana; Mahmud Yunus (Pendekar : Jurnal Pendidikan Berkarakter, 2024)
This study aims to show how plyometric jump to box and hurdle jump exercises affect the jump height of Gerzy Star Soccer School players. The study used a static group pretest-posttest design in pre-experimental research. A total of 22 soccer players who met the researchers' inclusion and exclusion criteria were selected through purposive sampling. Based on the results of the study, it was found that plyometric jump to box and hurdle jump exercises can increase the height of the player's jump. The results of the analysis showed that plyometric hurdle jump training was more efficient than plyometric jump to box training in increasing the jump height of players at Gerzy Star Soccer School. There was an increase in normal jump height of 6.7 cm between pretest and posttest with the significance of plyometric jump to box exercise was 0.000 < 0.05. Meanwhile, plyometric hurdle jump training also has a significance number of 0.000< 0.05 which proves a significant comparison, with the jump height generally increasing by 7 centimeters between the time before and after the test. Therefore, it can be concluded that plyometric jump-to-box and hurdle-jump guidance are efficient in increasing the jump height of Gerzy Star Soccer School players, but plyometric hurdle jump training is more efficient than plyometric jump to box guidance.